Research Progress of TiCN, TiAlN and TiAlCN Coatings - WU Yong, YANG Hanzhe, SUN Qingyun, CHEN Hui, XIA Siyao (Cailiao Baohu, 2023)
Hard coatings such as TiAlCN can improve the surface hardness， wear resistance and corrosion resistance of metal workpieces，thereby effectively improving the precision and service life of cutting tools， abrasive tools and auto parts in service under high-speed rotation conditions.In this paper， the structure and application of TiCN， TiAlN and TiAlCN coatings formed by adding Al and C elements to TiN were reviewed， the effects of adding Al and C elements on the structure and properties of the coatings and their mechanism of action were summarized.The preparation methods of TiCN， TiAlN and TiAlCN coatings in recent years were summarized， including DC magnetron sputtering(DCMS)， high power impulse magnetron sputtering (HiPIMS)， medium temperature chemical vapor deposition (MTCVD) and laser chemical vapor deposition (LCVD).In addition， the future development direction of multicomponent TiN coatings was prospected.